VALIDITAS DAN KEPRAKTISAN BUKU ILMIAH POPULER LIMBAH AIR KELAPA TUA SEBAGAI ZPT ALAMI PERTUMBUHAN SAWI (Brassica juncea L.) - Nida Zahra Al Banna; Najimatul Ilmiyah; Khairunnisa Khairunnisa (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
Popular scientific books are included in the learning resources. Popular scientific books are types of knowledge books whose discussion is based on research results. This book has a simple, short, and clear language arrangement to make it easier for all people to understand. This study aims to describe the validity and practicality of popular scientific books of old coconut water waste as a natural growth regulator for mustard green (Brassica juncea L.) growth. This research uses the type of EDR (Educational Design Research) research with Tessmer's formative evaluation design which is limited in several stages, namely self-evaluation, expert review, and one-to-one evaluation. This study used validity and practicality instruments. The results showed that the validity of popular scientific books was declared very valid with a value of 85.80%. Meanwhile, for the practicality of popular scientific books, it obtained a score of 88.33% with an excellent category.